Odour concentration affects odour identity in honeybees - Wright, Geraldine A (The Royal Society, 2005)
The fact that most types of sensory stimuli occur naturally over a large range of intensities is a challenge to early sensory processing. Sensory mechanisms appear to be optimized to extract perceptually significant stimulus fluctuations that can be analysed in a manner largely independent of the absolute stimulus intensity. This general principle may not, however, extend to olfaction; many studies have suggested that olfactory stimuli are not perceptually invariant with respect to odour intensity. For many animals, absolute odour intensity may be a feature in itself, such that it forms a part of odour identity and thus plays an important role in discrimination alongside other odour properties such as the molecular identity of the odorant. The experiments with honeybees reported here show a departure from odour-concentration invariance and are consistent with a lower-concentration regime in which odour concentration contributes to overall odour identity and a higher-concentration regime in which it may not. We argue that this could be a natural consequence of odour coding and suggest how an ‘intensity feature’ might be useful to the honeybee in natural odour detection and discrimination.